Pollution haven hypothesis (PHH) - Burcu Ozcan (Elgar Encyclopedia of Energy Economics, 2025)
Context Missing demographic data in electronic disease reporting systems are a national challenge. Accurate race and ethnicity data are vital for identifying health disparities, assessing health equity, and evaluating public health interventions. Program We piloted a matching process to enhance demographic completeness for 3 diseases (hepatitis, influenza, campylobacteriosis) by linking individuals across 4 New York State public health surveillance systems (NYSIIS, eCR, CDESS, ECLRS). Implementation Missing race and ethnicity data captured from this matching process were used to update our communicable disease surveillance system and were incorporated into the New York Hepatitis Elimination and Epidemiology Data set (HEED) and sent to the Centers for Disease Control and Prevention (CDC). Evaluation Integrating multiple surveillance sources substantially improved race and ethnicity completeness. Pairwise comparisons showed variable agreement across systems, with the highest concordance between eCR and ECLRS (κ = 0.70; 95% CI: 0.69-0.72) and between NYSIIS and eCR (κ = 0.70; 95% CI: 0.68-0.71). Ethnicity agreement exceeded that of race, with the strongest alignment between eCR and NYSIIS (κ = 0.83; 95% CI: 0.82-0.85). Discussion This project highlighted 3 key findings. First, matching significantly improved demographic completeness, especially for influenza and campylobacteriosis cases. Second, NYSIIS provided the most reliable demographic data, highlighting the importance of source quality. Third, improvements varied by disease, with smaller gains for hepatitis. Reliable race and ethnicity data are essential for identifying disparities, guiding targeted interventions, and ensuring equitable resource distribution. This approach demonstrates that linking existing surveillance systems can efficiently improve demographic data completeness without new infrastructure investments. As a cost-effective, scalable model, it provides a framework for enhancing data quality, promoting equity, and supporting data-driven decision-making in public health.